Study on Seismic Analysis of Multi Storey RCC Building With Mass Irregularities Using NBC 105:2020 (International Journal of Innovative Research in Engineering & Management, 2022)
Most of the multi-storey buildings are  analysed based on an assumption that the structure is  subjected to whole load after modeling the entire  structure. But in reality, each storey is subjected to some  assumed loads to act during construction period itself as  they are constructed in stages as storey wise. Sequential  analysis in a structure is ignored by many structural  engineers while analysing the structure. Because of this  ignorance, variation may occur in structural members in  the below storey with respect to above storey as the  construction proceeds which leads to incorrect  distribution of forces in the member. So, analysis has to  be done only by sequential application of loads in each  storey for the safety of the structure and cost effectiveness. In order to study the structural behavior of  a 10-storey building with mass irregularity has been  modeled and analyzed by equivalent static method using  different structural systems in CSI ETABS V16 as per  NBC 105:2020. Finally, results such as axial force, shear  force, overturning moment are drawn for the structural  members and response such as storey displacement,  storey shear and storey drift are plotted and compared for  each structural system
Keywords: Displacement; Base Shear; Seismic Analysis; Storey Drift; Overturning Moment